Nilai-Nilai Pendidikan Karakter dalam Gerak Tari Batok di Sanggar Seni Mutiara Minang di Kota Padang - Intan Sani Ashari; Indrayuda Indrayuda (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to describe the values ​​of character education and reveal the meaning of the character values ​​contained in the Batok dance at the Mutiara Minang Dance and Music Art Studio. This type of research is qualitative research using descriptive methods. The instrument for this research is the researcher himself and is assisted by supporting instruments such as writing equipment and a camera. Data was collected through literature study, observation, interviews and documentation. The steps to analyze data are collecting data, identifying data, classifying data, describing data and concluding data. The results of the research show that the Batok Dance at Sanggar Mutiara Minang contains character education values. So that it can be used as a lesson for the surrounding community and dance performers. Learning in this case is an effort to build character that is applied to oneself and the wider community. The character education values ​​contained in the Batok Dance at Sanggar Mutiara Minang can be classified as character education values ​​related to God, others and oneself. Batok Dance at the Mutiara Minang Art Studio teaches that humans should always be connected to God. The character values ​​of his relationship with God consist of worshiping God, begging God, giving thanks to God, surrendering to God. In the values ​​of character education, it is related to responsibility, teaching people to be responsible for every action and activity they carry out. In the values ​​of character education, the relationship with ourselves is that we must not give up on something, curiosity encourages us to correct mistakes and become better. Because curiosity makes us more insightful individuals who know what to do and what not to do.